A theoretical frame work and principles for the establishment and management of civil society organization in Vietnam - Nguyễn, Mạnh Cường (Hanoi, 2009)
This guidebook was prepared to respond to the needs of civil society development in Vietnam. Along with the economic renovation process, democratic governance and social harmonization in Vietnam have motivated active participation of civil society organizations in the development of public services provision, providing feedback in the consultation process, and assessing development policies.